2019
DOI: 10.1111/jnu.12513
|View full text |Cite
|
Sign up to set email alerts
|

Using Implementation Science to Further the Adoption and Implementation of Advance Care Planning in Rural Primary Care

Abstract: Advance care planning (ACP) is the process of guiding patients' selection of preferences for end-of-life care. It includes receiving information on the types of lifesustaining treatments available, deciding what types of treatment are wanted or not wanted, sharing personal values with loved ones, and completing an advance directive (National Hospice and Palliative Care Organization, n.d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
1
24
1
Order By: Relevance
“…To our knowledge this is the first study to explore ACP in Australian general practice using the TDF, and our use of an implementation sciences framework may assist in developing interventions to increase the uptake of ACP in dementia in primary care. Of the 14 TDF domains, the ones we found to be most relevant to the practice of ACP correlated with those of a scoping review by a research group in the US (Nelson-Brantley et al 2020), which also found social/professional role and identity, as well as environmental context and resources, to be important determinants in initiating ACP.…”
Section: Discussionmentioning
confidence: 61%
“…To our knowledge this is the first study to explore ACP in Australian general practice using the TDF, and our use of an implementation sciences framework may assist in developing interventions to increase the uptake of ACP in dementia in primary care. Of the 14 TDF domains, the ones we found to be most relevant to the practice of ACP correlated with those of a scoping review by a research group in the US (Nelson-Brantley et al 2020), which also found social/professional role and identity, as well as environmental context and resources, to be important determinants in initiating ACP.…”
Section: Discussionmentioning
confidence: 61%
“…Our system serves a mixed-rurality population, and rurality constraints (e.g., gaps in palliative care availability and longer travel distances for care) may further reduce ACP feasibility. [7] Predicting mortality using clinician gestalt alone may have limited accuracy, but combining gestalt with a predictive model may be synergistic. [14] Therefore, to help prioritize ACPs when resources are limited, and to encourage clinicians to have ACPs in those more likely to bene t, we developed a model to predict mortality occurring 5-to-90 days after the start of an inpatient admission.…”
Section: Background and Signi Cancementioning
confidence: 99%
“…A multidisciplinary approach seems to be the most appropriate to ensure a broad, multidimensional and individualised ACP process [12]. Specifically, primary care (PC) professionals have been recognized as the most suited to promote ACP processes, since the long-term nature of the relationships between PC professionals and patients is unique compared to other fields within the public health system [13][14][15]. This characteristic might help PC professionals build trust with patients, and it could explain the positive attitudes expressed to ACP process and its value on the improvement of the end-of life process [16].…”
Section: Introductionmentioning
confidence: 99%